The Effect Of Green Banking Activities On Green Banking Performance Mediated By Sustainable Green Financing - Thesalonica, Tennie; Setyawan, Ignatius Roni (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the determinants of green banking performance, specifically green banking activities mediated by sustainable green financing, by comparing conditions before and after Covid-19 amidst the phenomenon of banking digitalization. The researchers hypothesize a significant and positive relationship between green banking activities, green banking performance and sustainable green financing, as well as a significant and positive relationship between sustainable green financing and green bank performance. Additionally, the researcher examines the differences in the impact of green banking on sustainable green financing and green bank performance before and after COVID-19. The research method used is Ordinary Least Square with the Causal Step method to test the mediation variable and Moderated Regression Analysis to test the moderation variable using SPSS. The results of this study have important implications and can serve as a reference for banks in Indonesia in identifying factors that influence green bank performance and as a consideration in the development of green banking in the future, given the limited research on this topic in Indonesia.